"It does not help to look young and dumb…": Ageism and intergenerational contact in the Norwegian technical industry. Issue 3 (16th April 2018) - Meinich, Jenny; Sang, Kate
Abstract : Purpose: While age is receiving increased attention in the literature on workplace diversity, it remains under researched. Intergenerational contact and its relationship to ageism require further research to understand their mechanisms and impacts. The paper aims to discuss this issue. Design/methodology/approach: Using semi-structured interviews in the Norwegian technical industry, this paper explores how generations are formed and how this influences intergenerational contact. Findings: Through the lens of ageism, the findings reveal that generational stereotypes are strongly held by respondents, and may affect how members of the generations interact in the workplace. Further, the data demonstrate that both age and generation are socially constructed, and age discrimination is perceived by both older and younger workers. Originality/value: The study has relevance for managers who are overseeing organizations with considerable age differences.